2012
DOI: 10.1111/j.1748-1716.2012.02448.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Ca2+ channel blockers and isoproterenol on L‐type Ca2+ current in canine ventricular cardiomyocytes

Abstract: The results indicate that the action of isoproterenol is different in the presence of organic and inorganic Ca(2+) channel blockers. CoCl(2) and MnCl(2) were able to fully prevent the effect of isoproterenol on Ca(2+) current, while the organic Ca(2+) channel blockers failed to do so. This has to be born in mind when the effects of organic Ca(2+) channel blockers are evaluated either experimentally or clinically under conditions of increased sympathetic tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, the recovery of both current amplitude and kinetics indicate a limited relevance within the time-frames considered, if at all present. Other works [10,18,60] using similar experimental protocols have also reported limited current rundown effects.…”
Section: Limitationsmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the recovery of both current amplitude and kinetics indicate a limited relevance within the time-frames considered, if at all present. Other works [10,18,60] using similar experimental protocols have also reported limited current rundown effects.…”
Section: Limitationsmentioning
confidence: 70%
“…Test recordings in the presence of the drug were performed after >3 min from the beginning of drug exposure. Afterwards, ISO was washed out for >5 min to achieve a full washout of ISO, as reported in previous works [10,18], and measurements were repeated.…”
Section: Experimental Datamentioning
confidence: 99%
“…Moreover, TA caused hyperpolarizing shift of the steady‐state inactivation curve, which accelerates the voltage‐dependent inactivation of the Ca 2+ currents and prevents longer term free intracellular Ca 2+ increases. Nifedipine is a well‐known calcium channel blocker; Farkas et al found that nifedipine at 5 μM shifted the activation and inactivation curves of I Ca‐L toward the left direction (Farkas et al ., ). Because contractile activation is controlled by the Ca 2+ transient (i.e.…”
Section: Discussionmentioning
confidence: 99%